Constituição de valores de ciência e cultura no Brasil (1948-1988) - Marina Assis Fonseca (2012)
This dissertation explores the representations about the values associated to science and scientific culture in the discursive practices of the Brazilian Society for the Progress of Science (BSPS), during 40 years between 1948 and 1988. The methodology adopted consisted in the analysis of the content of such practices and of the speeches held at public events, especially in the Societys annual meetings, editorials and articles from the Ciencia e Cultura (Science and Culture) and Ciéncia Hoje (Science Today) as well as from interviews of BSPS's commemorative publications, on the occasion of its 50º anniversary and its 60º anniversary . The analysis was structured through references of sociology and philosophy: norms by Robert Merton (1942), counter-norms proposed by Ziman (2000) and categorizations done by Hugh Lacey (1998). The analysis circumscribed three historicalphases of the BSPS, linked to the issue of research. On the first phase, going from 1949 to 1964, impartiality and disinterest emerged as the main values associated to science. On the second phase, from 1964 to 1979, values of autonomy and freedom were emphasized, andon the third, between 1979 and 1988, commitment and democracy stood out. This study presents associations between values, actions and speeches by key members of BSPS amidst the historical contexts of the Brazilian political scene and of scientific development in the country, looking to emphasize the imperatives of scientific ethos that stood out and to describe how they were configured. It was concluded that the meaning of neutrality of science for the BSPS has been linked to its stand points on politics and the relationship between the latter and science, and that the image of such neutrality undenzvent a transformation, over 40 years, that went from the stated desire of political impartiality to theenhancement of the scientists social responsibility by means of his/her engagement on the definition of scientific policy and as a communicator of science to the general public. Finally, it is considered that BSPS played an important role in the construction of a legendary image about academic science. Finally, it is considered that the BSPS played an important role in building a legendary image on the subject of academic science.